Evaluasi Status Kesuburan Tanah pada Lahan Kering Berbasis Sistem Informasi Geografis pada Daerah Aliran Sungai Tukad Oos Kabupaten Gianyar, Bali - Gunawardhani, Ni Putu Monica Bhuana; Trigunasih, Ni Made; Soniari, Ni Nengah; Arthagama, I Dewa Made; Narka, I Wayan; Saifulloh, Moh (Agrotrop : Journal on Agriculture Science, 2024)
Evaluation of Soil Fertility Status on Dry Land Based on Geographic Information System in Tukad Oos River Basin, Gianyar Regency, Bali. Declining soil fertility can significantly impact soil productivity. Factors contributing to decreased soil fertility include the long-term use of inorganic fertilizers at constant doses, leading to nutrient depletion in the soil. This condition adversely affects the soil's physical, chemical, and biological properties. The purpose of this study is to assess soil fertility status, create a distribution map of soil fertility status, identify limiting factors, and provide soil management recommendations for the Oos Watershed Dry Land. The research methods employed include soil surveys and tests, with fertility status parameters such as Cation Exchange Capacity (CEC), Base Saturation (BS), organic carbon, total phosphorus, and total potassium. The results indicate that the soil fertility status at the study location is low (Land Units I, II, IV, VI, and VII) and medium (Land Units III and V). The limiting factors for soil fertility status were organic carbon, total phosphorus, total potassium, and CEC. To improve soil fertility in the Tukad Oos Watershed, it is recommended to increase the addition of organic matter and apply SP36 and KCl fertilizers on dry land.